Financial literacy of village owned enterprises (BUMDes) managers: A study of BUMNag managers in West Sumatra Province - Rita Rahayu; Indah Permata Suryani; Abdul Karib; Viya Guziana Sari (Jurusan Manajemen Fakultas Ekonomi Universitas Negeri Padang, 2022)
This study investigates the level of financial literacy of Village Owned Enterprises (BUMdes) managers in West Sumatra and identifies the determinant factors that affect their financial literacy. This study involves 208 BUMDES managers in West Sumatra province. Using an online questionnaire, we found that the literacy level of these BUMDES financial managers is categorized as 'less literate.' Furthermore, using SPSS to process the data, we found three determining factors that affect the level of financial literacy of BUMDes managers: age, educational background, and total income. This study found that the educational background is the sole determinant that has a positive and significant influence on these BUMDes managers’ financial literacy, while the other factors have less significant influence. The results of this study contribute to providing an overview to the government, especially the West Sumatra regional government, regarding the financial literacy condition of BUMDES managers, so that local governments and other related parties can consider this financial literacy factor in making policies related to the development of BUMDES. The implication of this research is that the West Sumatra regional government needs to focus more on the development of BUMDES Human Resources (HR) through formal education or non-formal education such as training, workshops or seminars, especially related to financial literacy. With good financial literacy, of course, it will be able to guide BUMDES managers in making good financial planning and management as well, which will certainly lead to improving the welfare of BUMDES.